Os serviços de extensão agrária pública ao pequeno agricultor familiar do distrito de Boane - Moçambique - Mubai, Boaventura Almeida (2014)
The public policies aimed to rural areas implemented in the post-independence period in Mozambique, prioritized from the beginning (1975), the agriculture fostered in the large estates at the expense of small family production. However, the socioeconomic and political changes that followed after initiation of political opening, gave subsidies to the creation in 1987 of the Public Agricultural Extension Program, resulting in a new direction of public policies, which now began to contemplate the segment of family farmers. Against this context the present work sought to diagnose the State actions through this program, in order to verify if such actions have contributed and contribute to the strengthening and income generation of farmers in this segment. Besides the bibliographical and documentary review, the research adopted a quantitative approach implemented on a field survey, realized by application of semi-structured questionnaires in the form of interviews, involving a sample of about one hundred and eighteen (118) small producers located in the district of Boane; and it was qualitative when by using interviews deepen the information gathered through the questionnaires. The systematization of the data was taken in Sphinx Lexical software - V5, and favored the representation of information through graphics allowing a broad reading of the studied fact. The analyses of the data collected, allowed to reach the following conclusions: a) that the Public Agricultural Extension Program could bring positive effects to the agricultural smallholders development, since its scope and encouragement for this category of producers is efficient and sufficient; b) The absence of significant differences in farm income between assisted agricultural producers and unassisted suggests reviewing and immediate improvement loans; c) The producers demonstrate an associational and/or cooperative interest in the organization of its production, but such interest is not being properly availed by extension practices in order to accomplish the technical and financial autonomy of these produces; d) the precarious agricultural infrastructure, the low education, the older age, and the uncertainty over land tenure, can affect the management and administration of agricultural production units, resulting in rural exodus.